Identification of tRNA-derived small RNAs and their potential roles in porcine skeletal muscle with intrauterine growth restriction - Gan, Mailin; Ma, Jianfeng; Chen, Lei; Zhang, Shunhua; Niu, Lili; Zhao, Ye; Li, Xuewei; Pan, Hongmei; Zhu, Li; Shen, Linyuan (Frontiers in Physiology, 2022)
Intrauterine growth restriction (IUGR) in humans often manifests as poor growth and delayed intellectual development, whereas in domestic animals it results in increased mortality. As a novel epigenetic regulatory molecule, tRNA-derived small RNAs (tsRNAs) have been reported to be involved in many biological processes. In this study, pigs were used as a model to characterize tsRNAs by sequencing in normal and IUGR porcine skeletal muscle. A total of 586 tsRNAs were identified, of which 103 were specifically expressed in normal-size pigs and 38 were specifically expressed in IUGR pigs. tRF-5c accounted for over 90% of tsRNAs, which were significantly enriched in IUGR pigs than in normal-size pigs. Enriched pathways of differentially expressed tsRNAs target genes mainly included metabolic pathways, Rap1 signaling pathway, endocytosis, mTOR signaling pathway, and AMPK signaling pathway. Regulatory network analysis of target genes revealed that IGF1 was one of the most important molecules of regulatory nodes in IUGR and normal porcine skeletal muscle. In addition, IGF1 was found to be one of the target genes of tRF-Glu-TTC-047, which is a highly expressed tsRNA in IUGR pigs. The findings described herein uncover the role of tsRNAs in IUGR porcine skeletal muscle development, thus providing insights into the prevention and treatment of IUGR in mammals.